AKUNTABILITAS GEREJA DALAM PANDANGAN ALKITABIAH DAN STEWARDSHIP THEORY DI GKPB KASIH KARUNIA SAMBANGAN - Ade Riani Dorkas Kedoh; Ni Luh Gede Erni Sulindawati (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the church's financial management and accountability at GKPB Kasih Karunia Sambangan in the biblical view and the view of stewardship theory. In this study, researcher used qualitative research. Data collection methods used are interviews, observation, and documentation studies. Data analysis in this study was carried out through several stages: data reduction, presenting data, interpreting, and concluding. The subject in this study is head of the Congregation, Management, Treasurer, and Member of GKPB Kasih Karunia Sambangan. Meanwhile, the object in this study is church financial accountability from a biblical view and stewardship theory at GKPB Kasih Karunia Sambangan. The results show that the church's financial management using a vertical accountability system or accountability to God is carried out by managing church cash honestly and with full responsibility and horizontal accountability or efforts to convey the treasurer to the congregation for the financial management that has been carried out.